2008
DOI: 10.1016/j.foreco.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Net primary productivity of Bruguiera parviflora (Wight & Arn.) dominated mangrove forest at Kuala Selangor, Malaysia

Abstract: The net primary productivity of Bruguiera parviflora dominated mangrove forest at Kuala Selangor, Malaysia was estimated from the average yearly biomass increment and litter production. The average yearly biomass increment in saplings and trees was 0.58 and 16.51 t ha À1 , respectively, and the annual amount of total litter production was 10.35 t ha À1 . The biomass increment in saplings and trees was not significantly different (t-test, p > 0.05) in 2 successive years and the estimated net primary productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 18 publications
(21 reference statements)
1
14
1
Order By: Relevance
“…Norhayati and Latiff (2001) also reported 115.56 t ha −1 of biomass for mixed mangrove (R. apiculata, R. mucronata, B. gymnorrhiza, B. parviflora, C. tagal, X. granatum) forests in Langkawi Island, Malaysia. In this present study, the level of aboveground biomass R. apiculata was lower compared to those reported by Christensen (1978); Gong and Ong (1990); Hossain et al (2008) and Norhayati and Latiff (2001) globally (Table 2). The proportions of biomass in this present study are unlikely among all components of R. apiculata.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Norhayati and Latiff (2001) also reported 115.56 t ha −1 of biomass for mixed mangrove (R. apiculata, R. mucronata, B. gymnorrhiza, B. parviflora, C. tagal, X. granatum) forests in Langkawi Island, Malaysia. In this present study, the level of aboveground biomass R. apiculata was lower compared to those reported by Christensen (1978); Gong and Ong (1990); Hossain et al (2008) and Norhayati and Latiff (2001) globally (Table 2). The proportions of biomass in this present study are unlikely among all components of R. apiculata.…”
Section: Discussioncontrasting
confidence: 78%
“…However, Heryati et al (2011) mentioned that the amount of the stem biomass is closely related to the production of trees obtained through photosynthesis which is generally stored in the trunk. Similarly, Hossain et al (2008) reported the same proportions of biomass stem>branch>leaf>reproductive components for B. parviflora in Kuala Selangor, Malaysia Table 3. All biomass proportion values found for R. apiculata in this present study are comparable with other studies elsewhere Table 3.…”
Section: Discussionmentioning
confidence: 70%
“…Considering that the development of allometric models for biomass estimation assumes minimization of errors and maximized accuracy, it is desirable that the selected models present minimum SEE and maximum R 2 a values. As presented before, the models that were under logarithmic transformation were the only ones to meet the assumptions of normality and homogeneity of variances and they also showed better adjustment and lower standard errors, which is in agreement with the findings of CLOUGH; SCOTT (1989), ONG et al (2004MAcGUINNESS (2005) and HOSSAIN et al (2008). This pattern explains why the non-transformed equations were discarded from the analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Mangroves are the dominant woody vegetation of intertidal coastlines in the tropical, sub-tropical and warm temperate zones of the world (Mahmood et al 2008), and these plants are constantly subjected to salinity ranging from seasonally freshwater (with traces of salinity) to hypersaline conditions (Ye et al 2005, Nguyen et al 2015. Salinity is known to limit propagule germination, seedling growth, and survival of mangroves (Mahmood et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits, consequently, may come either in May-July or in December-February, and each fruit contains approximately 4-6 semi-triangular seeds. Both fruits and seeds are buoyant and water dispersed, and seeds show epigeal germination (Mahmood 2015). Seed germination is greater in less saline conditions (approximately 60%) than in high saline conditions (approximately 20% - Mahmood et al 2014a).…”
Section: Introductionmentioning
confidence: 99%